Microenvironmental innate immune signaling and cell mechanical responses promote tumor growth. - Zhou, J.; Valentini, E.; Boutros, M. (Developmental Cell, 2021)
Tissue homeostasis is achieved by balancing stem cell maintenance, cell proliferation and differentiation, as well as the purging of damaged cells. Elimination of unfit cells maintains tissue health; however, the underlying mechanisms driving competitive growth when homeostasis fails, for example, during tumorigenesis, remain largely unresolved. Here, using a Drosophila intestinal model, we find that tumor cells outcompete nearby enterocytes (ECs) by influencing cell adhesion and contractility. This process relies on activating the immune-responsive Relish/NF-?B pathway to induce EC delamination and requires a JNK-dependent transcriptional upregulation of the peptidoglycan recognition protein PGRP-LA. Consequently, in organisms with impaired PGRP-LA function, tumor growth is delayed and lifespan extended. Our study identifies a non-cell-autonomous role for a JNK/PGRP-LA/Relish signaling axis in mediating death of neighboring normal cells to facilitate tumor growth. We propose that intestinal tumors "hijack" innate immune signaling to eliminate enterocytes in order to support their own growth.